Audit Report Lag in Manufacturing: Profitability, Characteristics, Governance Impact: Laporan Audit Terlambat pada Perusahaan Manufaktur: Dampak Profitabilitas, Karakteristik Perusahaan, dan Tata Kelola - Selly Nurfatimah; Sarwenda Biduri (Academia Open, 2023)
This quantitative research aims to examine the influence of profitability, company characteristics, and corporate governance on the audit report lag in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2018. The population consists of 138 manufacturing companies, and a purposive sampling technique is employed to select a sample of 58 companies. Quantitative data in the form of company annual reports from 2016 to 2018 are collected and analyzed using multiple linear regression analysis. The results reveal that profitability significantly affects the audit report lag in manufacturing companies during the specified period. However, the characteristics of the company and corporate governance do not show a significant impact on the audit report lag. These findings provide valuable insights for stakeholders and regulators in understanding the factors influencing audit report timeliness in the manufacturing sector, contributing to the improvement of financial reporting practices and corporate governance mechanisms. Highlights: This quantitative study investigates the impact of profitability, company characteristics, and corporate governance on the audit report lag in manufacturing companies. The research focuses on companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2018, utilizing a purposive sampling technique. Findings reveal that profitability significantly affects the audit report lag, highlighting the importance of financial performance in timely audit reporting for manufacturing firms. However, company characteristics and corporate governance do not show a significant influence on the audit report lag, suggesting the need for further examination of these factors' role in the manufacturing sector's financial reporting practices. Keywords: Profitability, Company Characteristics, Corporate Governance, Audit Report Lag, Manufacturing Companies.